Funkcja i struktura – dwie koncepcje języka w filozofii Wilfrida Sellarsa - Matuszkiewicz, Maria (Hybris, 2016)
Wilfrid Sellars’ presented two parallel conceptions of language: functional role semantics and theory of picturing. The aim of my paper is to consider how these two views fit together and what roles they play in his overall philosophical project. First I show philosophical motivations for adopting these conceptions. Functional role semantics contributes to explanation of mental phenomena, it is consistent with Sellar’s critique of the given, it provides a nominalistic account of abstract terms. The picturing theory explains how language can be about the world. The question I also address in this paper is to what extent both of these conceptions are marked by what is the key problem for Sellars - the indispensability of both naturalistic and normative perspective for an adequate account of cognition, intentionality and language. I try to trace the limits of naturalistic explanation in both of his conceptions.